The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.31545/intagr/117622
|View full text |Cite
|
Sign up to set email alerts
|

Field phenotyping of plant roots by electrical capacitance – a standardized methodological protocol for application in plant breeding: a Review

Abstract: A b s t r a c t. Due to the absence of a suitable method and standardized procedures, the root systems of plants have been evaluated to a much lesser extent than aboveground organs. The aim of this article is (i) to provide a detailed description and thus standardization of an upgraded procedure of electrical capacitance measurement for evaluating the size of the root system of plants in situ, which allows for a reassessment to be made during the growing season and subsequent harvest of seeds for the planting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…To enhance the effects, additional rounds of selection could potentially be useful to increase genetic gain to a magnitude that results in practically relevant increases in competitive ability. For this purpose, an additional selection tool for roots is selection by means of electrical capacitance, as this allows non-destructive field sampling [55]. However, this method also has limitations such as the influence of soil moisture on electrical capacitance.…”
Section: Outlook For Future Breedingmentioning
confidence: 99%
“…To enhance the effects, additional rounds of selection could potentially be useful to increase genetic gain to a magnitude that results in practically relevant increases in competitive ability. For this purpose, an additional selection tool for roots is selection by means of electrical capacitance, as this allows non-destructive field sampling [55]. However, this method also has limitations such as the influence of soil moisture on electrical capacitance.…”
Section: Outlook For Future Breedingmentioning
confidence: 99%
“…Tomographic methods such as magnetic resonance imaging (MRI), X-ray computed tomography (X-ray CT), and positron emission tomography (PET) provide detailed 3D imaging of plants, but these methods are expensive, slow, and often require plants to be grown in containers that are then passed through a scanning machine [11,12]. Electrical geophysical methods, such as those based on electrical impedance and electrical capacitance, are faster and cheaper than tomographic methods but require electrodes to be inserted into the soil, which restricts the number of plants that can be sampled [13,14]. Ground penetrating radar (GPR) is an ultrawideband, short-range electromagnetic wave-based technology that is popular in civil engineering, hydrology, and archaeology, and has been utilized to characterize the coarse roots of trees and shrubs [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Figure13. Correlations at depth between pod biomass (yield) and the GPR features presented in Table3.…”
mentioning
confidence: 99%
“…The measurement of root electrical capacitance (C R ) is a promising, rapid in situ technique capable of screening numerous plants at different growth stages. Moreover, the sampled plants can be harvested at maturity to determine GY and can also be used for reproduction (Středa et al, 2020). The C R method was successfully applied in the field to evaluate the effect of dwarfing genes on the RSS of barley (Chloupek et al, 2006), in order to select barley and wheat genotypes for higher RSS and drought tolerance (Chloupek et al, 2010;Svačina et al, 2014;Heřmanská et al, 2015), to assess the root diversity and water use of wheat varieties (Středa et al, 2012;Nakhforoosh et al, 2014), and to estimate canola RSS in relation to lodging resistance (Wu and Ma, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Conceptual models consider the roots to be imperfect cylindrical capacitors, in which the amount of electric charge stored by the polarizable membrane dielectrics depends on the root-soil interfacial area (Dalton, 1995). Even though some of the underlying biophysical principles are still unclear and there are uncertainties about the relative contribution of proximal and distal (fine) roots to the magnitude of the C R detected (Dietrich et al, 2012;Ellis et al, 2013;Cseresnyés et al, 2020;Peruzzo et al, 2020), several pot and field trials have convincingly demonstrated the efficiency of the capacitance method (Středa et al, 2020). One advantage of the technique is that, as the C R value is affected not only by the size but also by the histological properties of the roots (e.g.…”
Section: Introductionmentioning
confidence: 99%